2001
DOI: 10.1038/sj.bmt.1703134
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced graft-versus-tumor effect following dose-reduced conditioning and allogeneic transplantation for refractory lymphoid malignancies after high-dose therapy

Abstract: Summary:Non-myeloablative regimens have been proven to allow engraftment following allogeneic stem cells transplantation (allo-SCT) with minimal procedure-related toxicity. Conventional allo-SCT may produce remissions in patients with relapsed and refractory lymphoid malignancies (LM) but these good results may be achieved at the cost of high treatment-related morbidity and mortality. Application of allo-SCT using less intensive regimens may temper the frequency of these complications, allowing a potent graft-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…34,35 Patients with lymphoid malignancies have generally been transplanted in more advanced disease status and have received a greater number of therapy lines than those with myeloid disease. 34,36 Allo-HSCT in this setting is thus a greater challenge for physicians and investigators.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Patients with lymphoid malignancies have generally been transplanted in more advanced disease status and have received a greater number of therapy lines than those with myeloid disease. 34,36 Allo-HSCT in this setting is thus a greater challenge for physicians and investigators.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] The rationale behind this strategy is to decrease the high TRM observed after myeloablative allo-SCT, though preserving the GVT effect. In addition, RIC allo-SCT allows patients with significant coexistent medical problems to undergo allo-SCT.…”
Section: Non-myeloablative or Ric Allo-hsctmentioning
confidence: 99%
“…Some observations, including the initial report from our group, suggested that the kinetic and risk factors for infections might be modified after RIC allo-SCT. [17][18][19][20] However, our current knowledge of infectious complications after allo-SCT is still primarily based on results of analyses performed in the standard allo-SCT setting. This report describes an analysis of infectious complications (CMV antigenemia, documented bacteremia and fungal infections) in 101 patients with hematological and nonhematological malignancies, who received an antithymocyte globulin-(ATG), fludarabine-and busulfan-based RIC prior to allo-SCT from HLA-identical siblings.…”
Section: Introductionmentioning
confidence: 99%